2014
DOI: 10.1016/j.oooo.2012.07.486
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of cytotoxicity of hyaluronic acid as an extracellular matrix on OFCOL II cells by the MTT assay

Abstract: Results suggested a decrease in cell viability in the presence of HA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
(46 reference statements)
0
18
0
1
Order By: Relevance
“…HA is known as a biocompatible polymer and studies have shown that it is safe for concentrations up to 1-2% (W/V) [17,18]. Comparing the results obtained for the HA and HASSNH 2 polymers, no statistical differences were observed in all four tested situations.…”
Section: Polymer Modification Did Not Affect Cytotoxicitymentioning
confidence: 82%
“…HA is known as a biocompatible polymer and studies have shown that it is safe for concentrations up to 1-2% (W/V) [17,18]. Comparing the results obtained for the HA and HASSNH 2 polymers, no statistical differences were observed in all four tested situations.…”
Section: Polymer Modification Did Not Affect Cytotoxicitymentioning
confidence: 82%
“…Other researchers reported that the proliferation of cells cultured with the addition of high‐MW HA was not affected when compared with that of cells cultured without HA . However, other studies showed that the cell proliferation was inhibited with the presence of high‐MW HA . In one study, the researchers coated the culture plates with HA of varying MW under serum‐free conditions before cell culture, instead of direct addition of HA.…”
Section: Effect Of Ha On Cell Proliferation and Differentiation In Vitromentioning
confidence: 99%
“…Besides these receptors, some other factors have to be considered regarding the effect of MW and concentration of HA on cell proliferation and differentiation. On one hand, the delivering method of HA might play an important role . Different delivering methods of HA can lead to different length of HA–cell interaction time.…”
Section: Mechanism Of Ha On Cell Proliferation and Osteogenic Differementioning
confidence: 99%
See 2 more Smart Citations